Micro-structural analysis of time-variant evolution in pore geometry of cement materials during carbonation - Giannoukos, Konstantinos (2016)
The purpose of this project was to gain a fundamental understanding of the carbonation-induced alterations in borehole grouts. This was approached by determining the relationship between the chemical denaturation of the minerals in the evolving pore network and its associated transport properties. These changes resulted from material processing under a range of simulated underground temperatures, pressures and pH. The pore network geometry and transport properties were examined as a function of the degree of structural and mineral alteration. These alterations were then macroscopically related to the depth evolution of the carbonation fronts under elevated temperature and pressure conditions. The microstructure, pore geometry and transport properties were studied experimentally for class G cementitious grout samples immersed in CO2 saturated brine at 60ºC and 120ºC (80 bar) for durations up to 5 months. The evolution of the carbonation depth was captured by means of X-ray computed tomography (XRCT), the compositional changes were detected using scanning electron microscopy (SEM) coupled with energy dispersive X-ray analysis (EDXA) and X-ray diffraction (XRD) and finally the pore geometry was revealed using mercury intrusion porosimetry (MIP) and N2-physisorption. Temperature was the most sensitive variable to control the rate of alteration for both microstructure and pore network. Calcium leaching in the samples treated with N2-saturated brine was found to be a thermally dependent process; in fact the activation energy for Ca transport was found to be higher when increasing temperature from 60ºC to 120ºC. At temperatures higher than 60ºC full conversion of portlandite to other forms was justified on the grounds of activation energy and appeared to cause chemical instabilities within the grouts. Those instabilities where aggravated in the case of the carbonated brine. The examined carbonated samples showed two clearly defined areas (inner core and carbonated region) for any duration, that were separated by a clear demarcation line, namely the carbonation front. The time evolution of the carbonation depth was found to follow a power law equation that reflected the rate of diffusion for each temperature. At 60ºC the higher rate of diffusion led to faster local supersaturation conditions in the pores (with respect to Ca2+ and〖 HCO〗_3^-) justifying the growth of aragonite crystals. At 120ºC, the slower rate of diffusion was reflected by the growth of calcite. At 60ºC and 120ºC, both inner and carbonated parts exhibited a sealing stage (up to 1 month) and a dissolution stage (up to 5 and 3 months). The terms ‘sealing’ and ‘dissolution’ referred only for changes in the apparent porosity but in reality these changes were found to reflect the changes of the critical cavity to throat ratio due to different temperature and time. At 60ºC the permeability was proved to be controlled by the critical throats (big values of cavity/ throat ratio) and at 120ºC by the size of the critical cavity (small cavity/ throat ratio). The critical size of the pores and throats at 120ºC close to 12 nm, supported the unrestricted diffusion of calcium towards the outer and hence the faster buffering of the effluent bicarbonates. At 120ºC, the buffering was found to take place at the surface sites of the C-S-H particles and thus from structural Ca2+. At 60ºC the restricted transport of species due to the small critical throats (~4 nm) resulted in the big cavities which were the loci of aragonite crystallization from the free Ca2+. This distinction of ‘diffusion’ at 120ºC and ‘restricted transport’ at 60ºC, was the key point for the better fitting of the time evolution of the carbonation front to the x_C=A∙t^(1/2) at 120ºC. At the inner parts of the CO2 treated samples at 120ºC, in order the throats and cavities to resemble in size, the silicate matrix was suggested to experience simultaneously localized expansion (decreasing the cavity size) and shrinkage (throat enlargement). At 60ºC the preservation of the threshold diameter, the intensified ink-bottle phenomenon and same critical throats close to 3 nm, could have been caused due to: (1) the retarded pozzolanic reactions at 60ºC that would have caused the throats to be mechanically stable due to the microsilica particles and, (2) the small activation energy for the C-S-H particles to re-organize their structures and to align them leading to silicate condensation and polymerization. The plethora of existing oilwells sealed with ordinary Portland cements globally, dictates that the permeability of the entire well to CO2 fluids will rely on the diffusion among the pores of the C-S-H structures. The permeability values from this study (ranging from 70 μD to 0.1 μD) were found to allow for the efficient geological storage for CO2 across the entire range of temperatures studied but with different mechanisms of diffusion. The major significance of the present thesis was that it provided a better understanding of the relationship between the cement microstructure with its pore network parameters, a relationship that ultimately determined the permeability and extent of carbonation in the long term. In other words the aim of the thesis was fulfilled giving a more comprehensive image during carbonation of a class G oil well cement grout in a realistic scenario of geological storage of CO2, with temperature and time to be the only variables. The implications of the studied temperatures (60ºC and 120ºC) and durations (1, 3 and 5 months) in real CO2 injection wells, could provide better assessment of legacy injection wells (containing aged cement grouts) and more efficient design of new CO2 injection wells.